SOKOLSTVO IN UKRAINIAN REGIONS OF THE RUSSIAN EMPIRE: FROM ORIGIN TO DOWNFALL - Anna Prikhodko; Olha Kolomiitseva; Vira Prykhodko (University of Ljubljana Press (Založba Univerze v Ljubljani), 2020)
The purpose of this study is to advance a better insight into the history of Sokolstvo (Sokol movement) in the Ukraine within the territorial borders of the Russian Empire, and the variety of reasons for its origin and downfall. Slavic origin of Sokolstvo, the activity of supporters of Sokol gymnastics (SG) in the popularization of Sokol idea and, a gradual rapprochement of supporters of the two opposing areas of reforming Russia for further development began ("Slavophiles" and "Westerners") contributed to the emergence and rapid development of the Sokol movement in the Ukrainian regions of Russia. In the 90s of the 19th century, SG began to be cultivated in the Sokol units of gymnastic societies, since 1907 independent institutions began to open. By World War I, Sokol gymnastic societies (SGS) in Ukraine were the largest group. SGS constantly trained instructors, but the majority of SG teachers were foreigners, Czech by nationality. SG was officially introduced into the military training of the army and the curricula of secondary schools and cadet corps. Sokol events were a significant part of the public life of many Ukrainian cities. Representatives of Ukrainian regional societies became members of the Board of the Union of the Russian Sokol, founded in 1910. The crisis of the Sokolstvo began in the years of the World War I due to the growth of xenophobic attitudes. During the years of Soviet power, the Sokol were accused of a bourgeois orientation, recognized as the "hotbed of counter-revolution" and banned in 1923.